Hot rolled steel and method for producing same
By adjusting the chemical composition and thermal processing technology of steel, a suitable microstructure structure is formed, and the problem of insufficient corrosion resistance and tensile strength of steel in the chloride environment in the prior art is solved, thereby achieving efficient corrosion resistance and Mechanical properties.
Patent Information
- Application Number
- CN202280095633.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-12
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art cannot provide martensite aging steels with high tensile strength, low hardness and corrosion resistance in a chloride environment, and there are shortcomings in fatigue characteristics and economic processing.
By adjusting the chemical composition of steel, ensure the content of elements such as nickel, aluminum, titanium, chromium, etc., form intermetallic compounds to improve tensile strength and corrosion resistance, and avoid intermediate heat treatment during thermal machining and aging to ensure the steel Microstructure.
It has achieved tensile strength of steel above 1100MPa and hardness below 535Hv, and maintained a low corrosion rate in a chloride environment. It is suitable for industrial applications and improved the corrosion resistance and weldability of steel.
Smart Images

Figure BDA0005112633790000081 
Figure BDA0005112633790000091 
Figure BDA0005112633790000101
Abstract
Description
Technical Field
[0001] The present invention relates to hot rolled steels suitable for use in corrosive environments, particularly environments containing chlorides. Background Art
[0002] Early research and development in the field of high strength and high formability steels with corrosion resistance has resulted in several methods for steels, some of which are listed here for a conclusive evaluation of the present invention:
[0003] US20100037994 claims a method of processing a maraging steel workpiece, the method comprising receiving a maraging steel workpiece having a composition comprising 17 to 19 wt% nickel, 8 to 12 wt% cobalt, 3 to 5 wt% molybdenum, 0.2 to 1.7 wt% titanium, 0.15 to 0.15 wt% aluminum, and the balance iron and directly aging the maraging steel workpiece at the aging temperature to form precipitates within the microstructure of the maraging steel workpiece without any intermediate heat treatment between the thermomechanical working and the direct aging, wherein the thermomechanical working and the direct aging provide a maraging steel workpiece having an average ASTM grain size of 10. However, US20100037994 does not ensure corrosion resistance and only claims a method of economically processing maraging steel.
[0004] EP2840160 provides a maraging steel excellent in fatigue properties, the maraging steel containing, by mass%, C: ≤0.015%, Ni: 12.0% to 20.0%, Mo: 3.0% to 6.0%, Co: 5.0% to 13.0%, Al: 0.01% to 0.3%, Ti: 0.2% to 2.0%, O: ≤0.0020%, N: ≤0.0020%, and Zr: 0.001% to 0.02%, with the balance being Fe and unavoidable impurities. EP2840160 provides the required sufficient strength, but does not provide a steel having corrosion resistance in a chloride environment. Summary of the invention
[0005] The object of the present invention is to solve these problems by making available a hot rolled steel having:
[0006] - a tensile strength greater than or equal to 1100 MPa, and preferably greater than 1200 MPa,
[0007] - a hardness less than or equal to 545 Hv, and preferably less than or equal to 535 Hv,
[0008] - Corrosion resistant steels, wherein a steel is considered to be corrosion resistant when the thickness loss due to corrosion is less than 0.07 mm / year, preferably less than 0.06 mm / year.
[0009] In a preferred embodiment, the steel according to the invention may also exhibit a yield strength of 850 MPa or more.
[0010] Preferably, such a steel may also have good suitability for forming, in particular for rolling, as well as good weldability and paintability.
[0011] Another object of the invention is also to make available a method for manufacturing these panels that is compatible with conventional industrial applications while being robust to variations in manufacturing parameters.
[0012] The hot rolled steel sheet of the present invention may optionally be coated to further improve its corrosion resistance. DETAILED DESCRIPTION
[0013] The above objects and other advantages of the present invention will become more apparent through the detailed description of the preferred embodiments of the present invention.
[0014] The chemical composition of hot rolled martensitic steel contains the following elements, where each element is expressed in the weight percentage present:
[0015] Nickel is present in the steel at 5% to 16%. Nickel is an essential element for the steel of the present invention to impart strength to the steel by forming intermetallic compounds with aluminum and titanium during heating before tempering. Nickel is also effective in suppressing the formation of the ferrite phase to increase the ratio of the martensite phase and improve corrosion resistance. Nickel also plays a key role in forming reverse transformation austenite during tempering, which limits the hardness of the steel to 550Hv. However, less than 5% nickel will not be able to impart strength due to the reduced formation of intermetallic compounds, however, when nickel is present at more than 16%, it will form more than 10% reverse transformation austenite, which is also harmful to the tensile strength of the steel. The preferred content of nickel used in the present invention can be maintained at 6% to 15%, and more preferably 6.5% to 14%.
[0016] Aluminum is an essential element constituting 0.5% to 3% of the steel of the present invention. Aluminum improves the strength of the steel of the present invention by forming intermetallic compounds with nickel and titanium during tempering. Aluminum is an essential element for imparting corrosion resistance to the steel of the present invention. In addition, aluminum is also added to the molten state of the steel to clean the steel of the present invention by removing oxygen present in the molten steel to prevent oxygen from forming a gas phase. The preferred limit of aluminum is 0.8% to 2.5%, and more preferably 0.9% to 2%.
[0017] The titanium content of the steel of the present invention is 0.1% to 1%. Titanium forms intermetallic compounds to give strength to the steel. If titanium is less than 0.1%, the necessary effect cannot be achieved. The preferred content for the present invention can be maintained at 0.1% to 0.9%, and more preferably 0.2% to 0.8%.
[0018] Chromium is an essential element constituting 4% to 15% of the steel of the present invention. Chromium is an important element for ensuring corrosion resistance and stress corrosion cracking resistance in severe corrosive environments. In addition, chromium helps to effectively transform the steel microstructure into martensite during cooling after annealing. In order to obtain these effects, Cr must be included at least 4%. However, when the content exceeds 15%, ferrite is easily formed in the metal structure of the steel, and it is difficult to obtain a martensitic structure by quenching. Therefore, the preferred chromium content is 5% to 14%, and the more preferred range is 6% to 12%.
[0019] Carbon is present in steel at 0.0001% to 0.03%. Carbon is a residual element and comes from processing. Impurity carbon below 0.0001% is not possible due to process limitations, and the presence of carbon above 0.03 must be avoided because it reduces the corrosion resistance of the steel.
[0020] The phosphorus content of the steel of the present invention is 0.002% to 0.02%. Phosphorus reduces spot weldability and hot ductility, in particular due to its tendency to segregate or co-segregate at grain boundaries. For these reasons, its content is limited to 0.02%, and preferably below 0.015%.
[0021] Sulfur is not an essential element but may be contained in the steel as an impurity, and from the viewpoint of the present invention, the sulfur content is preferably as low as possible, but from the viewpoint of manufacturing cost, the sulfur content is 0.005% or less. In addition, if higher sulfur is present in the steel, it combines to form sulfides and reduces its beneficial effects on the steel of the present invention, so it is preferably less than 0.003%.
[0022] Nitrogen is limited to 0.01% to avoid aging of the material. Nitrogen forms nitrides with vanadium and niobium that impart strength to the steel of the present invention through precipitation strengthening. However, as long as nitrogen is present at more than 0.01%, it can form a large amount of aluminum nitride that is harmful to the present invention, so the preferred upper limit of nitrogen is 0.005%.
[0023] Cobalt is an optional element for the steel of the present invention and is present at 0% to 7%. The purpose of adding cobalt is to help impart ductility to the steel. In addition, cobalt also helps to form intermetallic compounds of nickel by reducing the rate at which nickel forms a solid solution. However, when cobalt is present at more than 7%, it excessively forms reverse-transformed austenite, which is detrimental to the strength of the steel. The preferred content of cobalt for the present invention can be maintained at 0% to 6%, and more preferably 0% to 5%.
[0024] Molybdenum is an optional element constituting 0% to 6% of the steel of the present invention; molybdenum improves the strength of the steel of the present invention by forming intermetallic compounds with nickel and titanium during heating for tempering. Molybdenum contributes to the corrosion resistance characteristics achieved for the steel of the present invention. However, excessive addition of molybdenum increases the cost of addition of alloying elements, so for economic reasons, its content is limited to 6%. The preferred limit of molybdenum is 0% to 5%, and more preferably 0% to 4%.
[0025] Niobium is an optional element for the present invention. Niobium may be present in the steel of the present invention in an amount of 0% to 0.1% and is added to the steel of the present invention to form carbides or carbonitrides to impart strength to the steel of the present invention by precipitation strengthening.
[0026] Vanadium is an optional element constituting 0% to 0.3% of the steel of the present invention. Vanadium is effective in increasing the strength of the steel by forming carbides, nitrides or carbonitrides, and the upper limit is 0.3% for economic reasons. These carbides, nitrides or carbonitrides are formed during the second cooling step and the third cooling step. The preferred limit of vanadium is 0% to 0.2%.
[0027] Copper can be added as an optional element in an amount of 0% to 0.5% to increase the strength of steel and improve its corrosion resistance. A minimum of 0.01% copper is required to obtain such effects. However, when its content is higher than 0.5%, it may deteriorate the surface appearance.
[0028] The manganese content of the steel of the present invention is 0% to 2%. This element is a gamma-phase generating element (gammagenous). Manganese provides solid solution strengthening and suppresses the ferrite transformation temperature and reduces the ferrite transformation rate, thus contributing to the formation of martensite. However, when the manganese content is greater than 2%, it has an adverse effect, for example, it hinders the transformation of austenite to martensite during cooling after annealing. A manganese content greater than 2% may excessively segregate in the steel during solidification and the uniformity inside the material is impaired, which may lead to surface cracking during the hot working process. The preferred limit of the presence of manganese is 0% to 1%.
[0029] The silicon content of the steel of the present invention is 0% to 1%. Silicon is an element that contributes to improving strength by solid solution strengthening. Silicon is a component that can slow down the precipitation of carbides during cooling after annealing, so silicon promotes the formation of martensite. However, silicon is also a ferrite forming element and also increases the Ac3 transformation point, which will push the annealing temperature to a higher temperature range, which is why the silicon content is kept at a maximum of 1%. A silicon content higher than 1% may also cause temper embrittlement. The preferred limit of silicon presence is 0% to 0.5%, and more preferably 0% to 0.4%.
[0030] Other elements such as boron, oxygen or magnesium may be added individually or in combination in the following proportions by weight: boron ≤ 0.001%, oxygen ≤ 0.004%, magnesium ≤ 0.0010%. Up to the maximum content levels indicated, these elements allow the grains to be refined during solidification.
[0031] The remainder of the steel's composition consists of iron and unavoidable impurities resulting from processing.
[0032] The microstructure of steel contains:
[0033] Martensite constitutes at least 95% of the microstructure in terms of area fraction and is the matrix microstructure of the steel of the present invention. The martensite of the present invention may include both fresh martensite and tempered martensite. However, fresh martensite is an optional microstructural component, which is preferably limited to an amount of 0% to 4%, preferably 0 to 2%, and even better equal to 0% in the steel. Fresh martensite can be formed during cooling after tempering. Tempered martensite is formed by martensite formed during the second cooling step after annealing, and in particular after being below the Ms temperature, and more particularly at Ms-10°C to 20°C. Such martensite is then tempered during the holding period at a tempering temperature T tempering of 450°C to 680°C. The martensite of the present invention imparts ductility and strength to such steel. Preferably, the content of martensite is 96% to 99%, and more preferably 96% to 98%.
[0034] Reversed austenite is present in the steel of the present invention at 1% to 5% by area fraction. Reversed austenite is formed by the transformation from martensite to austenite during tempering of the steel and is also enriched and stabilized by nickel at the same time. The reversed austenite of the steel of the present invention imparts both hardness and corrosion resistance. Preferably, the content of reversed austenite is 1% to 4%, and more preferably 1% to 3%.
[0035] Intermetallic compounds of nickel, titanium and aluminum are present in the steel of the present invention. The intermetallic compounds are formed during heating to the tempering temperature and during the tempering process. The intermetallic compounds formed are both intergranular intermetallic compounds and intragranular intermetallic compounds. The intergranular intermetallic compounds of the present invention are present in both martensite and reversed austenite. The shape of these intermetallic compounds of the present invention can be cylindrical or spherical. The intermetallic compounds of the steel of the present invention are formed as Ni3Ti, Ni3Al or Ni3(Ti,Al) intermetallic compounds. The intermetallic compounds of the steel of the present invention give the steel of the present invention strength and corrosion resistance, especially corrosion resistance to chloride environments. However, when G-phase intermetallic compounds such as Ti6Si7Ni are present in the steel 16 or Mn6Si7Ni 16When the steel is present, they increase the hardness of the steel to more than 550 Hv and are also detrimental to the corrosion resistance characteristics of the steel of the present invention. The G-phase also makes the steel brittle. Therefore, the steel of the present invention does not contain G-phase intermetallic compounds.
[0036] In addition to the above microstructures, the microstructure of the hot rolled steel sheet does not contain microstructural components such as ferrite, bainite, pearlite and cementite, but they may be present in trace amounts. Some trace amounts of iron intermetallic compounds such as iron-aluminum and iron-nickel may be present, but their presence has no significant effect on the in-use properties of the steel.
[0037] The steel of the present invention may be formed into seamless tubular products or steel plates or even structural or operating parts to be used in industries having harsh environments containing chlorides or any other industry having a corrosive environment.
[0038] In a preferred embodiment for illustrating the present invention, the steel plate according to the present invention can be produced by the following method. A preferred method comprises providing a semi-finished casting of a steel having a chemical composition according to the present invention. The casting can be made into an ingot, a billet, a bar or continuously in the form of a thin slab or a thin strip, i.e. having a thickness ranging from about 220 mm for a slab to tens of millimeters for a thin strip.
[0039] For example, a slab having the above chemical composition is produced by continuous casting, wherein the slab is optionally subjected to direct soft reduction during the continuous casting process to avoid center segregation. The slab provided by the continuous casting process can be used directly at high temperature after continuous casting, or can be first cooled to room temperature and then reheated for hot rolling.
[0040] The temperature of the slab subjected to hot rolling is preferably at least 1150°C and must be lower than 1300°C. In the case where the temperature of the slab is lower than 1150°C, an excessive load is applied to the rolling mill. Therefore, the temperature of the slab is preferably high enough so that hot rolling can be completed in the 100% austenite range. Reheating at a temperature higher than 1275°C results in a loss of productivity and is also industrially expensive. Therefore, the preferred reheating temperature is 1150°C to 1275°C.
[0041] Thereafter, the reheated slab is subjected to hot rolling. The hot rolling finishing temperature used in the present invention is 800°C to 975°C, and preferably 800°C to 950°C.
[0042] The hot rolled steel strip obtained in this way is then cooled from the hot rolling finish temperature to a cooling stop temperature CS1 of 10°C to Ms. The preferred CS1 temperature range is 15°C to Ms-20°C. The cooling rate CR1 from the hot rolling finish temperature to CS1 is preferably 1°C / sec to 100°C / sec. In a preferred embodiment, the CR1 for cooling after the hot rolling finish temperature is 1°C / sec to 80°C / sec, and more preferably 1°C / sec to 50°C / sec.
[0043] Thereafter, the hot rolled steel strip is heated to an annealing temperature TA of Ae3 to Ae3+350°C. The hot rolled steel strip is kept at the annealing temperature for a duration greater than or equal to 30 minutes. In a preferred embodiment, TA is Ae3+20°C to Ae3+350°C, and more preferably Ae3+40°C to Ae3+300°C. The heating is started from CS1 to the TA temperature at a heating rate HR1 of at least 1°C / sec, and in a preferred embodiment, the heating rate HR1 for such heating is at least 5°C / sec, and more preferably at least 10°C / sec or more.
[0044] The hot rolled strip is then cooled after holding at the annealing temperature, preferably at a cooling rate CR2 of 1°C / sec to 100°C / sec. In a preferred embodiment, the cooling rate CR2 for cooling after holding at the annealing temperature is 1°C / sec to 80°C / sec, and more preferably 1°C / sec to 50°C / sec. After annealing, the hot rolled strip is cooled to a temperature range CS2 of 10°C to Ms, and preferably, the CS2 temperature is 15°C to Ms-20°C. Fresh martensite is formed during this cooling step, and the cooling rate CS2 must be greater than 1°C / sec to ensure that the hot rolled strip is fully martensitic in nature.
[0045] The annealed hot rolled strip is then heated to a tempering temperature Ttemper at a heating rate HR2 of 0.1°C / sec to 100°C / sec, preferably 0.1°C / sec to 50°C / sec, and even more preferably 0.1°C / sec to 30°C / sec. Intermetallic compounds of nickel, titanium and aluminium are formed during this heating and during tempering. The intermetallic compounds formed during this heating and tempering are both intragranular and intergranular intermetallic compounds formed as Ni3Ti, Ni3Al or Ni3(Ti,Al). The tempering temperature Ttemper is 450°C to 700°C, wherein the steel is tempered for a duration of 30 minutes to 72 hours. In a preferred embodiment, Ttemper is 490°C to 690°C, and more preferably 500°C to 680°C. During the tempering hold, the fresh martensite is transformed into tempered martensite, and due to the presence of nickel, some amount of the fresh martensite is reversed to form reversed austenite. The reversed austenite formed during tempering is nickel-rich for the following reasons: within the tempering temperature range of the present invention, some of the intermetallic compounds formed during heating dissolve and enrich the austenite with nickel, and this nickel-rich reversed austenite is stable at room temperature.
[0046] Thereafter, the hot rolled steel strip is cooled to room temperature to obtain hot rolled steel.
[0047] Example
[0048] The following tests, examples, graphical illustrations and tables presented herein are non-limiting in nature and must be considered solely for purposes of illustration and will demonstrate the advantageous features of the present invention.
[0049] Steel plates made of steels with different compositions are summarized in Table 1, where each element is expressed in the weight percentage in which it is present and the remainder is iron and other process impurities, where the steels were respectively produced according to the process parameters as noted in Table 2. Thereafter, Table 3 summarizes the microstructures of the steels obtained during the tests, and Table 4 summarizes the evaluation results of the properties obtained.
[0050]
[0051]
[0052] Table 3
[0053] Table 3 illustrates the results of tests carried out according to standards on different microscopes, such as a scanning electron microscope, for determining the microstructure of both the steel according to the invention and the reference steel.
[0054] The surface fractions of the phases in the microstructure are determined by cutting specimens from the steel plate, polishing and etching with reagents known per se to expose the microstructure. The determination of the reversed austenite is carried out by XRD, while for martensite, dilatometry studies are carried out according to the publication by SMC Van Bohemen and J. Sietsma in Metallurgical and materials transactions, Vol. 40A, May 2009 -1059.
[0055] Record the results here:
[0056]
[0057] I = according to the invention; R = reference; underlined values: not according to the invention.
[0058] Table 4 illustrates the mechanical properties of both the inventive steel and the reference steel. To determine the tensile strength and hardness, A25 type specimens were tested according to the NBN EN ISO 6892-1 standard.
[0059] The corrosion resistance test is carried out according to the accelerated chloride corrosion resistance test, in which the thickness of the steel sample is measured in millimeters (mm), and then such steel sample is immersed in a chloride solution with a chloride concentration of 1000 ppm at a temperature of 20° C. for a duration of one week. The steel sample is then taken out after one week. Thereafter, the thickness of the steel sample is measured again. The difference in thickness of the steel sample represents the loss of steel due to corrosion, and it is expressed in mm / year. Therefore, the more the thickness decreases, the more the steel is prone to corrosion; and the less the thickness decreases, the corrosion resistance.
[0060] The results of various mechanical tests performed according to the standard are summarized.
[0061] Table 4
[0062]
[0063] I = according to the invention; R = reference; underlined values: not according to the invention.
Claims
1. A hot rolled steel having a composition comprising the following elements expressed in weight percentage: 5% ≤ Nickel ≤ 16% 0.5%≤Aluminum≤3% 0.1%≤Titanium≤1% 4% ≤ chromium ≤ 15% 0.0001%≤Carbon≤0.03% 0.002%≤Phosphorus≤0.02% 0%≤Sulfur≤0.005% 0%≤Nitrogen≤0.01% and can include one or more of the following optional elements: 0%≤Cobalt≤7% 0%≤Molybdenum≤6% 0%≤Niobium≤0.1% 0%≤Vanadium≤0.3% 0%≤Copper≤0.5% 0%≤Manganese≤2% 0%≤Silicon≤1% 0%≤Boron≤0.001% 0%≤Oxygen≤0.004% 0%≤Magnesium≤0.0010% The remainder is composed of iron and inevitable impurities caused by processing, and the microstructure of the steel plate comprises at least 95% of martensite, 1% to 5% of reversed austenite, and intermetallic compounds of aluminum, titanium and nickel in terms of area fraction.
2. The hot rolled steel according to claim 1, wherein the composition contains 6% to 15% nickel.
3. The hot rolled steel according to claim 1 or 2, wherein the composition contains 0.8% to 2.5% aluminum.
4. The hot rolled steel according to any one of claims 1 to 3, wherein the composition contains 5% to 14% chromium.
5. The hot rolled steel according to any one of claims 1 to 4, wherein the composition contains 0.1% to 0.9% titanium.
6. The hot rolled steel according to any one of claims 1 to 5, wherein the intermetallic compound of aluminum, titanium and nickel is at least one or more selected from Ni3Ti, Ni3Al or Ni3(Ti,Al).
7. The hot rolled steel according to any one of claims 1 to 6, wherein the reverse transformed austenite is 1% to 4%.
8. The hot rolled steel according to any one of claims 1 to 7, wherein the steel has a tensile strength of 1100 MPa or more and a hardness equal to or less than 545 Hv.
9. A method for producing hot rolled steel comprising the following steps in sequence: - Providing a steel composition according to any one of claims 1 to 5; - reheating the semi-finished product to a temperature of 1150° C. to 1300° C.; - rolling the semi-finished product in the austenitic range to obtain a hot rolled steel strip, wherein the hot rolling final rolling temperature should be 800° C. to 975° C.; - then the hot rolled strip is cooled to a temperature CS1 of 10°C to Ms; - thereafter heating the hot rolled steel strip to an annealing temperature TA of Ae3 to Ae3+350° C. at a heating rate HR1 of at least 1° C. / s, and keeping the hot rolled steel strip at the TA temperature for at least 30 minutes; - then cooled at a rate of 1°C / s to 100°C / s to a temperature CS2 in the temperature range of 10°C to Ms; - thereafter reheating the hot rolled steel strip to a tempering temperature T tempering of 450°C to 700°C at a heating rate HR2 in the range of 0.1°C / s to 100°C / s, and keeping the hot rolled steel strip in the tempering temperature range for 30 minutes to 72 hours; - The hot rolled steel strip is then cooled to room temperature to obtain hot rolled steel. 10 . The method according to claim 9 , wherein the annealing temperature TA is Ae3+20° C. to Ae3+350° C.
11. The method according to any one of claims 9 or 10, wherein the tempering temperature Ttemper is 490°C to 690°C.
12. The method according to any one of claims 9 to 11, wherein the heating rate HR2 for tempering is 0.1°C / sec to 50°C / sec.
13. The method according to any one of claims 9 to 12, wherein the hot rolling finishing temperature is 800°C to 950°C.
14. Use of the steel according to any one of claims 1 to 8 or the steel produced according to the method according to claims 9 to 13 for manufacturing structural or operating parts for industrial use with harsh environments.
15. A seamless pipe, tube or part obtainable according to claim 14.
Citation Information
Patent Citations
Maraging steel excellent in fatigue characteristics
EP2840160A2
Method of processing maraging steel
US20100037994A1
